Membrane lipidome reorganization correlates with the fate of neuroblastoma cells supplemented with fatty acids. - Andrea Bolognesi (Public Library of Science (PLoS), 2013)
Palmitic acid is known to be apoptotic for nervous cells but no data are available on membrane lipidome transformations occurring during its supplementation, although membrane lipids are clearly involved in the apoptotic signaling cascade. NB100 neuroblastoma cells were supplemented with palmitic acid and membrane fatty acids were isolated, derivatized and analysed by gas chromatography at defined time intervals. Parallely, cell viability, morphology, apoptosis, cPLA(2) and caspase activations were checked. Interestingly, under 150 µM supplementation the incorporation of palmitic acid was accompanied by the specific release of arachidonic acid. This event was timely correlated with cPLA(2) and caspases activations, and the time window of 60 minutes was envisaged for crucial membrane lipidome changes. The simultaneous addition of 50 µM oleic, 50 µM arachidonic and 150 µM palmitic acids to the cell cultures influenced membrane changes with suppression of caspase activation and maintenance of cell viability. These results highlight the role of the membrane asset with fatty acid remodeling and suggest the potential of lipid-based strategies for influencing cell response and fate in human diseases, such as neurodegenerative disorders or tumours.